Respuesta :
expand by multiplying √7x⋅√x and √7x⋅7√7
√7x(√x−7√7)=√7x⋅√x−√7x⋅7√7
You can make√7x into √7⋅√x
=√7⋅√x⋅√x−√7⋅√x⋅7⋅√7=√7⋅(√x)2−(√7)2⋅√x⋅7since squaring and square roots are opposite, they cancel
=√7⋅x−7⋅√x⋅7=x√7−49√xI hope the square root symbols worked. I had to copy and paste from word. Hopefully this is what you needed!
remember
[tex](\sqrt{a})(\sqrt{b})=\sqrt{ab}[/tex]
first distribute
[tex]\sqrt{7x^2}-7\sqrt{49x}=[/tex]
[tex](\sqrt{x^2})(\sqrt{7})-7(\sqrt{49})(\sqrt{x})=[/tex]
[tex]x\sqrt{7}-7(7)\sqrt{x}=[/tex]
[tex]x\sqrt{7}-49\sqrt{x}[/tex] is simlified form
to evaluate, we would need a value for x
[tex](\sqrt{a})(\sqrt{b})=\sqrt{ab}[/tex]
first distribute
[tex]\sqrt{7x^2}-7\sqrt{49x}=[/tex]
[tex](\sqrt{x^2})(\sqrt{7})-7(\sqrt{49})(\sqrt{x})=[/tex]
[tex]x\sqrt{7}-7(7)\sqrt{x}=[/tex]
[tex]x\sqrt{7}-49\sqrt{x}[/tex] is simlified form
to evaluate, we would need a value for x